Optimalisasi Kecerdasan Buatan dalam Pendidikan: Strategi untuk Mempertahankan Etika, Humanisasi, dan Esensi Pembelajaran di Era Digital - Nur Asiyah; Imelia Sahda Salsabilla (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
The development of digital technology, especially Artificial Intelligence (AI), has brought significant changes in the world of education. This technology offers a wide range of opportunities to improve the effectiveness and efficiency of learning through the personalization of materials, analysis of student data, and the automation of learning evaluations. However, the implementation of AI in education also faces a number of challenges, such as inequality of access to digital infrastructure, low technological literacy among educators, and ethical issues related to the privacy and security of student data. This study aims to analyze the potential, challenges, and implications of the use of AI in the education system through a literature study approach. The research method used is a literature review by reviewing various scientific articles, research reports, and relevant academic publications in the 2020–2025 range. The data were analyzed descriptive-analytically to identify key themes related to the use of AI in learning. The results of the study show that AI has great potential in supporting more adaptive, interactive, and individual needs-based learning of students. However, the success of its implementation is highly dependent on the readiness of digital infrastructure, the technological competence of educators, and regulations that regulate the ethical use of technology. In addition, this study emphasizes that AI should be positioned as a supporting tool in the learning process, not as a substitute for the role of teachers. Therefore, the integration of AI in education needs to be carried out in a balanced manner while maintaining humanistic values in the learning process. The findings of this research are expected to contribute to the development of more inclusive and sustainable educational technology implementation policies and strategies